MAKING E-MODULE ON PHYTOCHEMICAL UTILIZATION MATERIALS IN PHARMACETICS ORIENTED CHEMICAL LITERATION - Nola Permata Sari; Saepudin Rahmatullah; Neneng Windayani (UIN Sunan Gunung Djati Bandung, 2021)
The industrial revolution 4.0 brings changes to the world of education that demands innovation and the use oftechnology and information in learning. The purpose of this research is to produce a teaching material, namelyan electronic module (e-module) on the use of phytochemicals in the field of pharmaceuticals which is orientedtowards chemical literacy. The method used in this research is the Design Based Research (DBR) method. Theresulting e-module presents material in the form of various phytochemical compounds that have bioactivity asanti-cancer, anti-diabetic, and anti-inflammatory along with chemical literacy-oriented questions. The e-moduleis validated by three validators, namely material experts and multimedia experts. In general, the results of the emodule validation are declared valid with a rcount value of 0.77 and are included in the fairly high validity category.